Parents’ Perceptions of Selecting Language of Instruction for their Children’s Primary Education in Malaysia (LSP International Journal, 2017)
The study examines the influence of parents’ educational background on the selection of language of instruction for their children’s primary education and their beliefs on the impact of language of instruction on children’s academic capabilities, career prospect and personal characteristics. A survey was conducted on 400 Chinese parents with a child in primary one in Kuching, Sarawak. The results showed that the parents’ educational background influenced their choice of language of instruction for their children’s primary education. The Chinese-educated parents in Kuching are more likely to enrol their children in Chinese-medium schools while English- and Malay-educated parents prefer Malay-medium schools. The Chinese-educated parents choose Chinese-medium school as they believed that their children would have better career prospects, more useful qualifications, academic competencies, particularly in Mandarin, mathematics and science, and greater appreciation of Chinese culture. The Chinese-educated parents also believed that their children would be proficient in English and Bahasa Malaysia, hardworking, open-minded and racially tolerant but the English- and Malay-medium educated parents disagreed on these perceived impacts of Chinese education and believed that their children studying in Malay-medium schools are just as likely to have these characteristics. The findings suggest that parental choice of school language of instruction may be a proxy for choosing the school culture associated with Chinese- and Malay-medium schools.